Active Middle Ear Implantation: Long-term Medical and Technical Follow-up, Implant Survival, and Complications. Issue 5 (June 2016) - Zwartenkot, Joost W.; Mulder, Jef J. S.; Snik, Ad F. M.; Cremers, Cor W. R. J.; Mylanus, Emmanuel A. M.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To evaluate the long-term medical and technical results, implant survival, and complications of the semi-implantable vibrant soundbridge (VSB), otologics middle ear transducer (MET), and the otologics fully implantable ossicular stimulator (FIMOS). Study Design: Retrospective cohort study. Patients: Patients with chronic external otitis and either moderate to severe sensorineural or conductive/mixed hearing loss. Setting: Tertiary referral center. Intervention: Implantation with the VSB, MET, or FIMOS. Main Outcome Measures: Medical complications, number of reimplantations, and explantations. Results: Ninety-four patients were implanted, 12 patients with a round window or stapes application. 28 patients were lost to follow-up. The average follow-up duration was 4.4 years (range, 1 month–15 years). 128 devices were evaluated: (92 VSB, 32 MET, 4 FIMOS). 36 devices (28%) have been explanted or replaced (18 VSB, 14 MET, 4 FIMOS). Device failure was 7% for VSB, 28% for MET, and 100% for FIMOS. In 16 patients (17%) revision surgery (n = 20) was performed. Twenty patients (21%) suffered any medical complication. Conclusion: Medical and technical complications and device failures have mostly occurred in the initial period of active middle ear implants (AMEI) implementation and during clinical trials or experimental procedures. All four FIMOS had technical difficulties. An important decrease in the occurrence of both medical and technical complications was observed. Application in more recent years did not show any complications and the recent device failure rates are acceptable. Magnetic resonance imaging (MRI) incompatibility should be taken into account when indicating AMEI.